Anti-Diabetic Indole-Terpenoids From Penicillium sp. HFF16 Isolated From the Rhizosphere Soil of Cynanchum bungei Decne - Xiao, Na; Xu, Yiru; Zhang, Xinru; Li, Haonan; Zhang, Shengnan; Xiao, Ang; Yu, Jinyi; Yang, Mingtian; Lv, Fujin; Zhang, Mingyu; Hao, Gangping; Chen, Guotong; et al. (Frontiers in Chemistry, 2022)
Finding novel anti-diabetic compounds with effective suppression activities against hepatic glucagon response is urgently required for the development of new drugs against diabetes. Fungi are well known for their ability to produce new bioactive secondary metabolites. As part of our ongoing research, five new indole-terpenoids (1-5), named encindolenes D-H, were isolated from the fungus Penicillium sp. HFF16 from the rhizosphere soil of Cynanchum bungei Decne. The structures of the compounds were elucidated by spectroscopic data and ECD analysis. In the anti-diabetic activity assay, compounds 1-5 could inhibit the hepatic glucose production with EC50 values of 17.6, 30.1, 21.3, 9.6, and 9.9 μM, respectively, and decrease the cAMP contents in glucagon-induced HepG2 cells.